Role of ICT in Grassroots: A Review on Gram Panchayats of District Hisar in Haryana - Kumar, Suresh; Athavale, Vijay (International Journal of Computer Sciences and Engineering, 2025)
Whole the planet is international village currently on a daily basis, this is often a bit like a dream return true. In nineteenth and up to mid-20th century communication was primarily based mostly based on postal and telegram. Invention of radio, TV and telephone was developing within the field of communication. Globalization is just attainable because of satellite communication. Little or no to take advantage of total population is computer literate. Since the age of Sh. Rajiv Gandhi, numerous makes an attempt are created to market computer acquisition. It's up to some. We tend to square measure largest hardware producer in world. Bangalore is understood as Silicon Valley. Aloof from lucent image their square measure some areas wherever computer is simply sort of a TV. I belong to Haryana one in every of the superior state of the nation in per capita financial gain, acquisition rate, human right index. However, computer literacy isn't shows there. This paper is especially centered on computer and digital literacy among the gram panchayat representatives. It had been not as shining at we tend to thought call centers out sourcing centers at NCR. Most of the present time schemes of central and state government are operated the data communication. I attempted my uttermost in assortment and interpretation of information and genuineness. There's giant scope of improvement in implementation of digital acquisition to a layperson i .e. Manage labor, farmers, panchayat Representative, dairy farm farmers